2015
DOI: 10.2147/jpr.s80829
|View full text |Cite
|
Sign up to set email alerts
|

Different measures, different outcomes? Survey into the effectiveness of chronic pain clinics in a London tertiary referral center

Abstract: BackgroundChronic pain clinics aim to improve challenging conditions, and although numerous studies have evaluated specific aspects of therapies and outcomes in this context, data concerning service impact on outcome measures in a general pain population are sparse. In addition, current trends in commissioning increasingly warrant services to provide evidence for their effectiveness. While a plethora of outcome measures, such as pain-intensity or improvement scores, exist for this purpose, it remains surprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…However, our results also show that numerical-spatial changes are present across different painful conditions, hence adding considerably to the evolving field of research into the cognitive consequences of CP. Further, the proposed association between number sense alterations and pain intensity measurements could be criticized for not acknowledging enough the complex nature of clinical pain assessment ( Shah et al, 2015 ). Although it is certainly true that a patient’s subjective pain rating is influenced by a variety of factors, number sense might still be an important contributor, a notion clearly supported here.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results also show that numerical-spatial changes are present across different painful conditions, hence adding considerably to the evolving field of research into the cognitive consequences of CP. Further, the proposed association between number sense alterations and pain intensity measurements could be criticized for not acknowledging enough the complex nature of clinical pain assessment ( Shah et al, 2015 ). Although it is certainly true that a patient’s subjective pain rating is influenced by a variety of factors, number sense might still be an important contributor, a notion clearly supported here.…”
Section: Discussionmentioning
confidence: 99%
“…This approach maintains the focus on ‘the pain,’ as defined by the subjective rating, and the presumption that reducing the NPR will normalize the associated components including one’s quality-of-life. Despite the lack of correlation between statistically significant changes in the subjective pain rating and improvements in functioning ( McCracken et al, 2002 ; Jensen et al, 2004 ; Shah et al, 2015 ) as well as patient satisfaction with treatment ( Comley and DeMeyer, 2001 ), there appears to be a rigid adherence to changes in NPR scores as the primary indicator of therapeutic efficacy and effectiveness ( Farrar et al, 2001 ; Ballantyne and Sullivan, 2015 ; Sullivan and Ballantyne, 2016 ). Admittedly, the use of multidimensional outcomes is encouraged ( Gewandter et al, 2014 ), but they are frequently considered secondary to a reduction in the pain intensity rating.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the measure, 18%–25%reported a clinically important improvement (using MIC) in pain and quality of life. A study in a single UK tertiary pain centre using the same MIC calculations reported that 16%–23% of patients improved (Shah et al, ), a comparable proportion. Others have reported far greater improvement.…”
Section: Discussionmentioning
confidence: 92%